La extensión del ámbito subjetivo del derecho del trabajo - Gutiérrez-solar Calvo, Beatriz (Cuadernos de Relaciones Laborales, 2008)
The personal scope of Labour Law has always been forced to a strong expansive tendency with protective purposes. The criteria to make this extension has different roots, however it has always been respected the following limit: labour law shall be applied to those relationships where the worker is due to provide his services on behalf of the employer and under his legal authority. Currently these aspects are very important because the new Estatuto del Trabajo Autónomo will soon be approved. This means a revolution in this legal area, since self employees are going to be protected by rules that can be considered Labour Law, if the latest is considered as a wide and flexible theme.